Hashimoto Encephalopathy and Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
A 12-year-old boy with Hashimoto encephalopathy and drug-resistant status epilepticus responsive to plasmapheresis is reported from Ankara University Medical School, Turkey.